Romania : Technical Assistance Report-Enabling the Large Taxpayer Office to Reduce the Tax Gap. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Assistance report discusses measures for enabling Romania's Large Taxpayer Office (LTO) to reduce the tax gap. It recommends changing the criteria for inclusion of taxpayers in the LTO so that it is primarily based on turnover. The criteria should apply to taxpayers throughout Romania and should be the primary mechanism to establish whether a taxpayer is 'in or out.' It is also important to maintain or increase the current number of employees in the LTO, even though the new criteria may significantly reduce the LTO taxpayer population. Although the taxpayer population will be lower, its importance in terms of revenue that needs to be protected will increase.